The Potentials of Agricultural Policy and Spatial Planning Policy for Ecological and Economic Sustainable Rural Development - Kaufer, Ricardo; Krott, Max; Hubo, Christiane; Giessen, Lukas (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
European and german spatial planning policy and agricultural policy contain the policy objective to promote sustainable land use in rural areas. Both policies promise to promote comprehensive developments in rural areas, aiming at ecological target states, economic development, adaptation to economic globalization processes and strengthening regional stock flows to conserve resources. Analyzing these policies by testing their policy objectives and instruments in regard to sustainable land use delivers that only less instruments can support these objectives. Most instruments focus on economic development and adaptation to economic globalization processes. Ecological target states and strengthening regional stock flows are not supported by sufficient instruments.